Comparative civic culture : the role of local culture in urban policy-making - Reese, Laura A. (Laura Ann), 1958-; Rosenfeld, Raymond A. (Burlington, VT : Ashgate, 2012)
Comparative civic culture: theory and methods -- Categorizing civic cultures: testing a typology of local civic culture -- Inclusive/bureaucratic cities: Pittsburgh, Ottawa, Vancouver -- Partnerships in Pittsburgh: civic cultures and organizational capacities -- Civic culture in Ottawa: the endurance of local culture -- Vancouver: the sustainable city -- Market-active and passive cities: Charlotte, Calgary, Cleveland, Louisville -- Civic culture and corporate regime in Louisville -- A perpetual crisis: Cleveland's unfinished, changing, and incomplete civic agenda -- Civic culture as a policy premise: appraising Charlotte's civic culture -- Civic culture in Calgary: the oil and developers' land -- Individualistic cities: Dallas and Miami -- A tale of two cities: civic culture and public policy in Miami -- The civic culture of Dallas, Texas -- Conclusion: a theory of local civic culture.